The Impact of Government Expenditures on Unemployment: A Case Study of Jordan - Saraireh, Shadi (Asian Journal of Economic Modelling, 2020)
In this paper, we estimate the effects of Government spending on unemployment in Jordan for the period 1990 to 2019. By using the ARDL co-integration test we found a negative and statistically significant long-run relationship between government spending and the unemployment rate in Jordan. An increase in government spending by a per cent of GDP is found to reduce unemployment by about 0.43 percentage points in the same year. We also noticed that, in the short-run, government spending has a positive and significant impact on unemployment.